Absence of the impurity-resonance spot at a Bi defect located near the Zn impurity in Bi2Sr2Ca(Cu1-xZnx)2O8+δ - Wang, Zhaohui; Fan, Shengtai; Li, Han; Li, Huazhou; Yang, Huan; Wen, Hai-Hu (Frontiers in Physics, 2024)
Zn dopants to Cu sites in high-Tc cuprates strongly suppress superconductivity and act as impurities with a strong quasiparticle scattering resonance. Using the scanning tunneling microscope, we investigate the electronic structure in the atomic scale around Zn impurities in Bi2Sr2Ca(Cu1-xZnx)2O8+δ. The intense scattering resonance of the Zn impurity in the CuO2 layer strongly affects the measured local density of states of the BiO layer on the surface. The pattern of the bound state induced by a Zn impurity consists of a central spot at the Bi atom just above the Zn impurity and eight symmetric spots at the next nearest neighboring (NNN) and the third nearest neighboring (3NN) sites of Bi atoms. When the Bi atom above the NNN Cu atom is missing, the corresponding scattering spot is absent simultaneously. Our results indicate that the measured impurity-induced bound state pattern is strongly influenced by Bi atoms on the surface and therefore supports the "filter" theoretical model of the nonlocal interlayer tunneling effect from the CuO2 layer to the BiO layer on the surface. Our research provides extra information about the impurity-induced bound state by Zn impurities.